Difusión de la ingeniería clínica en eventos académicos - Gaitán-González, M. J.; Ortiz-Posadas, M. R. (Revista Mexicana de Ingenieria Biomedica, 2007)
Clinical Engineering has been seen as a professional activity but there is an academic divulgation interest that has made it to be included as a theme in biomedical engineering conferences. The papers presented in the last five years in academic events at national, Latin-American and international levels, were analyzed to observe the Clinical Engineering development and the tendencies that could be obtained form these presentations. According to the main Clinical Engineering activities, each work was classified. In total, 29 papers were presented in the national conference, 71 in the Latin-American and 317 in the international one. Most of the national conference works were on Technology Management, while for the Latin-American meetings were on Technology Assessment and in the international one, including telemedicine, on Technology Development. The medical assistance is changing from a mainly hospital environment to a diffuse one, spread into smaller health providers or even as homecare; this represents new challenges to Clinical Engineering to be solved.